(untitled) (Research, Society and Development, 2020)
Brazil has a considerable variety of species edible fruits, such as strawberry-guava (Psidium cattleianum), which has significant environmental plasticity and great potential for use. Studies related to reproductive biology, involving the knowledge of phenology are efficient tools to contribute to the improvement of species management and conservation strategies. Thus, this study aimed to monitor and record the phenological development of yellow and red Strawberry-guava, contrasting the differences between both. The study was developed in Dois Vizinhos, with red and yellow strawberry-guava, cultivar Ya-Cy, with branches marked at random, proceeding with photographic record and annotations of the peculiarities. The data were presented through images and a detailed description of each phase. The vegetative growth of the red strawberry-guava occurs between July and November, flowering between October and November with fruit ripening from late December to March. The vegetative growth of the yellow strawberry-guava occurs between July and October and between January and April, flowering from September to November and, January to March with fruit maturation between December and February and, from April to September. The red strawberry-guava produced only once a year, while the yellow strawberry-guava tree shows three outbreaks of production in the same period.